Evaluation of Anti-Xa Target Attainment with Prophylactic Enoxaparin Dosing Regimens for Venous Thromboembolism Prophylaxis in Morbidly Obese Patients - Andrew Sabers; Emilie Langenhan; Sean N. Avedissian; Brandon Reynolds (MDPI AG, 2024)
Subcutaneous enoxaparin has been shown to reduce the risk of venous thromboembolism (VTE) among hospitalized patients. However, alternative enoxaparin dosing strategies may be necessary in morbid obesity. The objective of this study was to assess the rate of target anti-Xa attainment with three enoxaparin dosing regimens for venous thromboembolism (VTE) prophylaxis in morbidly obese patients. In this retrospective study, anti-Xa target attainment was assessed among adult patients with a body mass index (BMI) ≥ 40 kg/m2 receiving enoxaparin 40 mg twice daily (BID), 60 mg BID, or 0.5 mg/kg BID. Univariate and multivariate analyses were conducted. Target anti-Xa levels were defined as a steady-state, peak level of 0.2-0.5 IU/mL. This study included 120 patients with 55 patients receiving 40 mg BID, 44 patients receiving 60 mg BID, and 21 patients receiving 0.5 mg/kg BID. Target anti-Xa levels were achieved in 29.1% of patients in the 40 mg BID arm, 54.5% in the 60 mg BID arm, and 90.5% in the 0.5 mg/kg BID arm. Anti-Xa target attainment was significantly increased in both the 60 mg BID arm (p = 0.01) and the 0.5 mg/kg arm (p < 0.0001), compared to the 40 mg BID arm. In morbidly obese patients, weight-based dosing was associated with a greater attainment of target anti-Xa levels. Further studies are needed to determine the impact of these dosing regimens on clinical outcomes.